Responses of Withania frutescens (L.) Pauquy (Solanaceae) Growing in the Mediterranean Area to Changes in the Environmental Conditions: An Approach of Adaptation - Moussaoui, Abdelfattah El; Bourhia, Mohammed; Jawhari, Fatima Zahra; Khalis, Hind; Chedadi, Mohamed; Agour, Abdelkrim; Salamatullah, Ahmad Mohammad; Alzahrani, Abdulhakeem; Alyahya, Heba Khalil; Alotaibi, Asdaf; Bousta, Dalila; Bari, Amina (Frontiers in Ecology and Evolution, 2021)
Background Flora growth is always influenced by the environmental conditions that surround the plant. The Objective of the Study The present research work was undertaken to study the response of Withania frutescens (L.) Pauquy to changes in the environmental conditions by investigating topographical, climatological, morphological, histological, and phytochemical aspects influencing the plant’s growth. Materials and Methods The topography of the study area was described using the Digital Terrain Model (DTM). The bioclimatic study was carried out using a climatological database (TerraClimate) used for an old period 1960–1970 (OP) and a new period 2000–2019 (NP). The histological study on stems, leaves, and roots was investigated according to protocols as described in the present study. The phytochemical analysis was assessed using a gas chromatograph coupled to a mass spectrophotometer after silylation. Results The topographical study showed that the selected stations varied in terms of topographical characteristics. The average annual precipitation recorded for the study area was 624 mm/year, and the thermal amplitude was around 34.64°C. The morphometrical study revealed that the plant had changes in length and width from one zone to another. The histometrical study of organs showed changes in tissue structure over time and location. The phytochemical content in the studied plants was also found to vary over time and location. Conclusion Based on the obtained results, we could confirm that W. frutescens has developed alternate strategies to mitigate increasingly harsh environmental conditions.